Analysis of the Main Products of the Proposed Complex of Preventive Tactical and Technical Aspects of Scar Surgery (Open Herald: Periodical of Methodical Research, 2024)
Despite modern advances in surgical techniques and biomedical technologies, the treatment of facial burns remains a difficult task, and the formation of post-burn scars may be inevitable. The approach to treating a burn wound begins with an accurate diagnosis of the depth and size of the burn, which is crucial for choosing the time and approach to treatment. Superficial burns (first degree) heal without surgery and, as a rule, do not lead to adverse scarring or hyperpigmentation, since the entire dermis is preserved. Superficial incomplete burns (second degree) usually heal spontaneously within a few days or weeks and can lead to scarring. Deep incomplete burns and burns of full thickness (third degree) usually require excision with reconstruction (often with skin grafting) and are more prone to the development of GTR. It is generally accepted that any burn that does not heal on its own within 3 weeks should be excised and transplanted as early as possible